1909 թվականի Կիլիկիայի հայկական կոտորածներն ըստ իտալական դիվանագիտական փաստաթղթերի - Բալոյան, Արամայիս (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The Italian diplomats, who eyewitnessed the massacres of the Armenian population in the provinces of Adana and Aleppo in April of 1909, have passed very notable information to the Italian government.
Keywords: Հայոց ցեղասպանություն; Հայոց պատմություն